Performance Enhancement Of Anaerobic Ammonium Oxidation Reactor Start-Up And Operation With The External Hydrazine Addition - Ganesan, G.Sivarajah (2019)
Anaerobic ammonium oxidation (Anammox) is one of the widely used biological treatments to remove nitrogenous compounds from wastewater. Despite this, Anammox system has long start-up period and the Anammox bacteria can easily undergo inhibition or starvation due to fluctuation of feed in wastewater treatment plants. In the first part of the study, Anammox bacteria were enriched in a sequencing batch reactor (SBR) with a working volume of 8L. In 75 weeks the substrates were increased step wise from 100 – 900 mg-N/L. The substrates provided (ammonium + nitrite) were in equimolar balance of 1:1. The parent SBR achieved more than 90% of nitrogen removal efficiency (NRE) in 14 weeks. The second part of the study was to investigate the effect of external hydrazine addition on aiding the start-up of Anammox reactor. Effects of 5 different externally added hydrazine concentration on reactor start-up were studied (0, 5, 10, 15, 20 mg/L). According to the results obtained, SBR with 10 mg/L hydrazine addition only took 7 weeks with an NRE of 86%. However, the SBR with no hydrazine addition took 11 weeks to stabilize with a NRE of 83.5%. The third part of the study was done to evaluate the effect of substrate inhibition on Anammox bacteria and ability of external hydrazine addition to aid the recovery of Anammox bacteria. 3 substrate concentrations were studied which were 900, 1100 and 1300 mg-N/L. The outcomes show that the inhibition percentage (IP%) obtained for reactors with substrate concentration of 900, 1100 and 1300 mg-N/L after 28 days of inhibition were 27, 38 and 75%, respectively. It was found that the substrate inhibition model (Edwards model) is the best model to represent the inhibition towards Anammox bacteria. Half saturation constant (Ks) and inhibition constant (KIE) obtained were 361.62 mg/L and 731.3 mg/L, respectively. During the recovery studies, reactors that had hydrazine addition showed better recovering capabilities compared to the one without hydrazine addition. The best result in terms of NRE was obtained from the reactor inhibited with 900 mg-N/L and recovered in the presence of hydrazine (R9H) which was 94%. Evidently, the best growth rate was also obtained from reactor R9H at 0.22/day and the lowest growth rate was obtained for R13 which was 0.07/day. The final part of this study was to evaluate the effect of different starvation condition on Anammox bacteria and its recovery. Three different starvation were studied which were starvation with the presence of ammonium (Ra), nitrite (Rn), and hydrazine (Rh). The decay rates calculated after 15 days for Ra, Rn, and Rh were 0.032/day, 0.042/day and 0.019/day, respectively. Finally, the best and the worst recovering capabilities after starvation were shown by reactor Rh and Rn where the growth rate value tabulated were 0.092/day and 0.011/day, respectively.